ANMCO POSITION PAPER: Considerations on in-hospital cardiological consultations and cardiology outpatient clinics during the COVID-19 pandemic. (27th August 2020) - Valente, Serafina; Colivicchi, Furio; Caldarola, Pasquale; Murrone, Adriano; Di Lenarda, Andrea; Roncon, Loris; Amodeo, Enzo; Aspromonte, Nadia; Cipriani, Manlio Gianni; Domenicucci, Stefano; Francese, Giuseppina Maura; Imazio, Massimo; et al.
Abstract: Infections by SARS CoV2 - COVID-19 have become in a short time a worldwide health emergency. Due to cardiovascular implications of COVID-19 and to very frequent previous cardiovascular disorders of COVID-19 patients, it is presently crucial that Cardiologists are fully aware of COVID-19 related epidemiological, pathophysiological and therapeutic problems, in order to manage at best the present emergency by appropriate protocols developed on the basis of the competences acquired and shared on the field. The aim of this document is to propose algorithms for the management of cardiovascular diseases during COVID-19 emergency with the objective of providing patients with optimal care, minimizing contagion risk and appropriately managing personal protective equipment.